Applied behavioral analysis in top level football: Theory and application - Tornberg, R.; Gustafsson, H.; Ekvall, D. (Football Psychology - From Theory to Practice, 2019)
Despite a strong research base and the potential for effective behaviour modification, the application of behavioural sport psychology in team sport is rarely described in the literature. Therefore, drawing on our experiences as sport psychology consultants the aim of this chapter is to provide a description of how applied behaviour analysis (ABA; Baer, Wolf, & Risley, 1968, 1987) can be applied in top-level football. ABA has extensive support from other contexts including behavioural problems in youth and organizational development and we have found it very useful in our work with athletes. First, behavioural sport psychology in relation to cognitive behavioural therapy (CBT) and psychological skills training (PST) will be discussed. Second, the seven dimensions of ABA will be described using examples from the football. Finally, the application of these dimensions is highlighted in a case of an elite football player experiencing anxiety and self-confidence issues. We also summarize the benefits of adopting a behavioural approach in football. With so few descriptions of ABA in sport, we hope this chapter could provide a useful start for practitioners.